Advances in Insulin Infusion Set in the New Era of Automated Insulin Delivery: A Systematic Review. (March 2023) - Zhang, Gina; Romo-Anselmo, Evan; Kwa, Tim; Cohen, Ohad; Vigersky, Robert; Chattaraj, Sarnath
Introduction: Automated insulin delivery (AID) has become a well-known research topic devoted to achieving better glycemic outcomes. AID systems consist primarily of three components: the continuous glucose monitoring system, the insulin delivery system, either tethered or patch pump, and the control system (algorithm). A key component in the tethered pump AID system is the insulin infusion set (IIS). This Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) study was conducted to evaluate the IIS evolution in the era of AID and to provide future perspectives of IIS clinical use. Methods: Literature searches for articles published from January 2016 to July 2022 were performed in Embase/Medline and PubMed. Data were extracted following PRISMA guidelines. Primary meta-analysis outcomes were IIS wear duration, total daily dose of insulin, and IIS failure reasons/modes. Results: We identified 387 publications, of which 15 eligible studies compared various IISs comprising over 1400 participants and >53 000 wears. Half of the studies published in 2022 were focused on extended IISs designed for wear durations of seven days or more. Three clinical trials have demonstrated the safe use of extended IISs to seven days of wear in individuals with type 1 diabetes, and two also demonstrated good glycemic control throughout the seven-day use. Conclusions: Research in insulin infusion technology has increased in the last six years, and extended IISs have demonstrated improved overall performance, particularly in duration of wear. Paths for future products are discussed with an emphasis on understanding the existing barriers related to both technical and nontechnical issues.